Percutaneous Lymphatic Embolization of Abnormal Pulmonary Lymphatic Flow as Treatment of Plastic Bronchitis in Patients With Congenital Heart Disease. Issue 12 (22nd March 2016) - Dori, Yoav; Keller, Marc S.; Rome, Jonathan J.; Gillespie, Matthew J.; Glatz, Andrew C.; Dodds, Kathryn; Goldberg, David J.; Goldfarb, Samuel; Rychik, Jack; Itkin, Maxim
Abstract : Background—: Plastic bronchitis is a potentially fatal disorder occurring in children with single-ventricle physiology, and other diseases, as well, such as asthma. In this study, we report findings of abnormal pulmonary lymphatic flow, demonstrated by MRI lymphatic imaging, in patients with plastic bronchitis and percutaneous lymphatic intervention as a treatment for these patients. Methods and Results—: This is a retrospective case series of 18 patients with surgically corrected congenital heart disease and plastic bronchitis who presented for lymphatic imaging and intervention. Lymphatic imaging included heavy T2-weighted MRI and dynamic contrast-enhanced magnetic resonance lymphangiogram. All patients underwent bilateral intranodal lymphangiogram, and most patients underwent percutaneous lymphatic intervention. In 16 of 18 patients, MRI or lymphangiogram or both demonstrated retrograde lymphatic flow from the thoracic duct toward lung parenchyma. Intranodal lymphangiogram and thoracic duct catheterization was successful in all patients. Seventeen of 18 patients underwent either lymphatic embolization procedures or thoracic duct stenting with covered stents to exclude retrograde flow into the lungs. One of the 2 patients who did not have retrograde lymphatic flow did not undergo a lymphatic interventional procedure. A total of 15 of 17(88%) patients who underwent an intervention had significant symptomatic improvement at a median follow-up of 315 days (range, 45–770 days). The most common complication observed was nonspecific transient abdominal pain and transient hypotension. Conclusions—: In this study, we demonstrated abnormal pulmonary lymphatic perfusion in most patients with plastic bronchitis. Interruption of the lymphatic flow resulted in significant improvement of symptoms in these patients and, in some cases, at least temporary resolution of cast formation.